(3GdYbO GdKejf aj JGQjN GdHdO GdCejfs - (3Jbi GdOjf eMeO Hf eMeO Hf CMeO Hf Ydj GdMSfj GdaGSi Gdecj,J (B832 (3g` s
(3ChdgG (B:s
(3jHJOF HZGdH Hf YjSi Hf CHj jhSa GdCfUGQi s
(3ai BNQ GdcJGH cJGHI HNW GdYdGeI eMeO GdeOYh HCHi GdNjQ agO GdgGTei Gdeci JajO SeGYg ai (B56 (3eLdSkG CKfGA SfI (B867s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B300s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B182 s
Keywords: (3GdJGQjNs